Fotografando digitalmente, pensando analogicamente: a caixa preta da fotografia numérica - Valle, Isabella Chianca Bessa Ribeiro do (2012)
In order to communicate efficiently it is necessary to dominate the languages we use. Photography is one of these languages, but some transformations have taken place during the shift from analogical to digital mechanisms, which demand a renewal of the photographer s knowledge and understanding: to unveil the numerical black box of photography. Nowadays, the photographer is in a migration process that, according to Stuart Hall, situates the migrant being between tradition and translation. Thereby, the negotiation between the traditional (analogical) and the new (digital) in the photographic universe is the main focus of this research. It was observed that, while photographing digitally, photographers still think analogically. Guided by familiar terms like ISO, grain, development, etc. their digital photos are captured, treated and manipulated through the options and tools available in the interfaces of the devices and programs that simulate previously known analogical processes. In a reality that deals with sensors and bits, terms and interfaces still related to chemical processes are used by photographers even when dealing with numerical photography. They are equipped with digital cameras and programs, but few of them understand the nature and the new creative and communicative potentialities of numerical photography beyond familiar interfaces. Thus, using the works of authors like Vilém Flusser, Ansel Adams, Edmond Couchot, Lev Manovich, Arlindo Machado, Giselle Beiguelman, Lucia Santaella, among others, as a background, not only did this research analyze the migration process of photography and the way photographers use the digital resources available in their cameras and computers, but also the communication configuration itself and the language used by the digital cameras and graphic programs. In order to do that, as a first step, from a description of the chemical and numerical processes, this work points out the essential changes between photographic practices (chemical and numerical) and in the photographic image itself. Such changes should also lead to a transformation in the creative process of photographs, for it is through technical and aesthetic choices that images are produced with certain communicative purposes. In a second step, the interfaces of DSLR cameras and graphics programs (Photoshop and Lightroom) were analyzed and it was also underscored that some limitations imposed by the interfaces of these devices cause stereotyping in photographs processed through standardized, automatic tools; repeating concepts of the analogical universe that no longer apply to the digital universe. And finally, as a third step, the answers to questionnaires given to photographers, which aimed to understand how the migrant photographers currently deal with these changes, were discussed and also used to capture some trends in digital thinking